2007
DOI: 10.1073/pnas.0703126104
|View full text |Cite
|
Sign up to set email alerts
|

T cell activation requires mitochondrial translocation to the immunological synapse

Abstract: T helper (Th) cell activation is required for the adaptive immune response. Formation of the immunological synapse (IS) between Th cells and antigen-presenting cells is essential for Th cell activation. IS formation induces the polarization and redistribution of many signaling molecules; however, very little is known about organelle redistribution during IS formation in Th cells. We show that formation of the IS induced cytoskeleton-dependent mitochondrial redistribution to the immediate vicinity of the IS. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
324
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(346 citation statements)
references
References 42 publications
19
324
1
2
Order By: Relevance
“…In agreement with previous studies (Quintana et al, 2007;Contento et al, 2010), Baixauli et al (2011) report that mitochondria accumulate at the IS following T-cell stimulation. They advance this model further and show that the fission factor DRP1 regulates mitochondria positioning close to the peripheral supramolecular activation cluster (pSMAC; Figure 1A), which together with the central SMAC form the IS in T cells.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies (Quintana et al, 2007;Contento et al, 2010), Baixauli et al (2011) report that mitochondria accumulate at the IS following T-cell stimulation. They advance this model further and show that the fission factor DRP1 regulates mitochondria positioning close to the peripheral supramolecular activation cluster (pSMAC; Figure 1A), which together with the central SMAC form the IS in T cells.…”
supporting
confidence: 93%
“…Mitochondria buffer Ca 2 þ at the IS thereby avoiding premature inactivation of the Ca 2 þ channels (Quintana et al, 2007). Baixauli et al (2011) report increased global Ca 2 þ signals following DRP1 impairment.…”
mentioning
confidence: 99%
“…We also see this when using BM-DCs, suggesting that centriole positioning is likely to play a more significant role in the helper T cell versus CTLs, perhaps because of the centrality of synaptic secretion to their function. In Jurkat T cells, mitochondria translocated to the cytoplasm just inside the plasma membrane when stimulated with anti-CD3-coated beads (41), but in our system mitochondria are scattered throughout the activated T cell. This difference may reflect the earlier stage of T-cell development of the Jurkat cell relative to the more mature T-cell blasts used here.…”
Section: Discussionmentioning
confidence: 92%
“…Alternatively, the caps may be sequestering channels to reduce Ca 2ϩ influx in areas outside of the IS. For example, if polarization of mitochondria, which import cytosolic Ca 2ϩ , produces a Ca 2ϩ gradient with low cytosolic Ca 2ϩ near the IS (Quintana et al, 2007), the CRAC channels in the cap would be in an area with the highest cytosolic Ca 2ϩ . This would inactivate the CRAC channels in caps, whereas cap formation removes channels from the areas near the IS, enhancing the Ca 2ϩ gradient.…”
Section: Discussionmentioning
confidence: 99%
“….1 cells on CD3, n ϭ 699; E6.1 cells on CD45, n ϭ 552; E6.1 cells on CD45 ϩ thapsigargin, n ϭ 487; E6.1 cells on CD45 ϩ thapsigargin ϩ ionomycin, n ϭ 550; 2-APB-treated E6.1 cells on CD3, n ϭ 489; EGTA-treated E6.1 cells on CD3, n ϭ 362; EGTAϩBAPTA-treated E6.1 cells on CD3, n ϭ 327; CCCP-treated E6.1 cells on CD3, n ϭ 445; PP2-treated E6.1 cells on CD3, n ϭ 356; JCaM1.6 cells on CD3, n ϭ 340; and Lck-reconstituted JCaM1.6 cells on CD3, n ϭ 259. and L). Some studies have reported a connection between mitochondrial activity and maintenance of CRAC currents (Quintana et al, 2006(Quintana et al, , 2007. We treated cells with CCCP to abolish mitochondrial potential, thus affecting both mitochondrial function and decreasing the magnitude of the CRAC current.…”
Section: Influx Of External Ca 2؉ Is Not Needed For Cap Formationmentioning
confidence: 99%